Development of interactive software (shear force and bending moment) - Wong, Jun Yan (Nanyang Technological University, 2022)
This Final Year Project’s goal is to create a software capable of rendering assistance to potential users in the analysis of a beam exposed to assorted load and support conditions while possessing interactive capabilities. It shall be capable of serving as a learning platform, as well as providing pertinent information in response to user interaction with the graphical user interface (GUI). Shear force and bending moment diagrams will also be generated to better visualize and convey the concept of shear force and bending moment for future learners. Python shall be utilized as the programming language to develop the software, part in due to its nature as a simplistic yet effective programming language. This would enable future developers to easily comprehend the algorithms of the software considering Python is commonly employed in various facets of the industry. The software’s capability includes the usage of pins, rollers, fixed supports, point loads, moments / torques and distributed loads. Furthermore, it shall be able to compute the cross-sectional area and moment of inertia of classic beam geometries such as I-shaped, H-shaped and hollow circular. The software will subsequently be converted into an executable application to facilitate user accessibility.